Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS): A case with adverse reaction to three drugs alternately administered - Manieri, Sergio; P Mirauda, Maria; De Gregorio, Fabiola; Colangelo, Carmela; Tagliente, Maria; Abate, Rosaria; Romaniello, Luciana; Lapolla, Rosa; Salvatore, Donatello (Journal of Advanced Pediatrics and Child Health, 2021)
Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a severe multiorgan hypersensitivity reaction mostly caused by several eliciting drugs in patients with a genetic predisposition. Incidence of DRESS in children is very variable, frome 1:1000 to 1:10.000, and the mortality rate seems to be lower than 10%. Anti-convulsants are the main drugs involved both in adults and in children. The treatment of choice is the prompt withdrawn of the offending drug and using intravenous immunoglobulins and corticosteroids used in synergy. In recent years, emerging studies have outlined the disease more clearly. We present a pediatric case in which the patient developed DRESS syndrome as a result of exposure to lamotrigine before and carbamazepine after and a relapse after exposure to omeprazole. Starting from this case report we provide an overview on DRESS Syndrome.